2011
DOI: 10.1007/s12630-011-9479-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the systemic toxicity of lidocaine versus its quaternary derivative QX-314 in mice

Abstract: In this in vivo animal study, the relative potencies of QX-314 for systemic CNS and cardiac toxicity were significantly higher than those of lidocaine. These data do not support the hypothesis that QX-314 is a safer local anesthetic compared with lidocaine in terms of systemic toxicity. Whereas our results do not exclude the possibility that QX-314 may represent a clinically useful agent to produce long-lasting local anesthesia and nociceptive blockade after a single shot in humans, its systemic toxicity relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
1
32
0
2
Order By: Relevance
“…4 However, it has been observed that intrathecally administered QX-314 caused irritation and death in mice, 6 whereas systemic administration caused central nervous system and cardiac toxicity. 7 In addition, irreversible nerve blockade is seen in animals administered with high concentrations of QX-314. 4 Because irreversible nerve dysfunction can be associated with severe local tissue toxicity, 1 we sought to determine whether QLD administration caused tissue injury.…”
Section: Conclusion: Coadministration Of Site 1 Sodium-channel Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, it has been observed that intrathecally administered QX-314 caused irritation and death in mice, 6 whereas systemic administration caused central nervous system and cardiac toxicity. 7 In addition, irreversible nerve blockade is seen in animals administered with high concentrations of QX-314. 4 Because irreversible nerve dysfunction can be associated with severe local tissue toxicity, 1 we sought to determine whether QLD administration caused tissue injury.…”
Section: Conclusion: Coadministration Of Site 1 Sodium-channel Blockmentioning
confidence: 99%
“…Compared with amino-amide local anesthetics, QLDs have a similar intracellular site of action 12 but are considered less permeable across the cell membrane. 7,13 Tetrodotoxin (TTX) and saxitoxin (STX) are naturally occurring neurotoxins that bind to site 1 on the extracellular part of the sodium channel 14 and effectively block peripheral nerve conduction. 15,16 Synergism has also been previously observed between site 1 blockers and tricyclic antidepressants.…”
Section: Conclusion: Coadministration Of Site 1 Sodium-channel Blockmentioning
confidence: 99%
“…31 Previous research has shown an ED50 for central nervous system and cardiac toxicity in mice of approximately 19.5 mg/kg and 21.2 mg/kg. 32 The cardiac side effects of lidocaine, contributed by the blockage of voltage-gated sodium channels, appear at plasma levels higher than 10 μg/ml in humans. 33 Considering the high ED50 for lidocaine in mice and extensive animal research in lidocaine toxicity with similar dosage, we did not measure plasma levels of lidocaine, and we have strong indications we stayed under critical plasma levels of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for its high water solubility, cardiac toxicity of QX-314 might also be weak because toxicity of local anesthetics on heart positively correlates with their hydrophobicity [19]. However, a recent study indicated that CNS and cardiac toxicities of QX-314 were similar or even more serious than that of lidocaine [20].…”
Section: Introductionmentioning
confidence: 99%